Trickle-down effects of temporal leadership: The roles of leadership perspective and identification with leader - Zhang, Yingying; Hu, Zhonghui; Tian, Siyu; Zhou, Chunyang; Ding, Yi (Frontiers in Psychology, 2022)
Based on social learning theory and the trickle-down effects, in which behavioral patterns cascade from one management level to the next (also known as the falling domino effect), we attempt to answer whether upper-level managers’ temporal leadership can be transferred to lower-level managers to form their temporal leadership, and what the mediating mechanisms and boundary conditions for this occurrence are. By analyzing the data from 234 middle-level managers and 686 junior managers/employees, we found that top managers’ temporal leadership was positively associated with middle-level managers’ temporal leadership through the mediating role of middle-level managers’ temporal leadership perspective and that the relationship was moderated by middle-level managers’ identification with the top manager. Identification with the top manager, in particular, strengthens both the top manager’s positive effect on middle-level managers’ temporal leadership and the top manager’s temporal leadership’s mediating role in this relationship through their temporal leadership perspective. The theoretical and managerial implications of these findings are investigated.